2020
DOI: 10.24235/al.ibtida.snj.v7i2.6676
|View full text |Cite
|
Sign up to set email alerts
|

Developing Edutainment-Based Comic Media in Integrative-Thematic Learning in the Elementary School

Abstract: The aim of this research is to develop edutainment-based comic media in thematicintegrative learning in fifth grade of elementary school. This study is a Research and Development (R&D) using the Borg and Gall model. The data were obtained through observation, interviews, and questionnaires. The results of comic media were obtained through a media expert product evaluation questionnaire and material from experts, educational practitioners, and peers. While the trial results were obtained through a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…(Egbert & Borysenko, 2018). The present study was in line with previous findings who found that instructional videos help students to understand material concepts that are too abstract (Fauyan, 2019;Febriyanti & Mustadi, 2020;Pahmi & Syahfutra, 2019). The selection of the Google Classroom application to access learning is also supported by other studies (Hikmatiar et al, 2020;Permata & Bhakti, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…(Egbert & Borysenko, 2018). The present study was in line with previous findings who found that instructional videos help students to understand material concepts that are too abstract (Fauyan, 2019;Febriyanti & Mustadi, 2020;Pahmi & Syahfutra, 2019). The selection of the Google Classroom application to access learning is also supported by other studies (Hikmatiar et al, 2020;Permata & Bhakti, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The media used by teachers when learning fine arts does not help students understand the material and does not attract students' attention. Comics are a medium in the form of books that present a story of (Febriyanti & Mustadi, 2020). Elementary students usually like digital comic illustrations so much that they are motivated and entertained to explore the contents of the comic (Rais et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…E. Sari & Suryana, 2019). Material aspects in the form of media which according to essential competencies and learning indicators lead to learning objectives, aspects of language media that have been adapted to improve spelling and language that are easily understood by thirdgrade elementary school students, and communicative aspects stimulate students to understand the storyline of fairy tales (Febriyanti & Mustadi, 2020;Moslehpour et al, 2018;Siregar et al, 2021). The application of interactive pictures and pictures based on the articulation storyline shows that the implementation of the development of interactive learning media based on the articulation storyline is a valid and practical medium for students from obtaining validation scores from media experts, material experts, design experts, and design experts.…”
Section: Discussionmentioning
confidence: 99%